THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, DISCIPLINE OF STUDENT AND INTEREST OF LEARNING WITH STUDENTS MATHEMATICS LEARNING OUTCOMES IN CLASS VII - Anis Agustiyana; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
Low student learning outcomes related to a variety of factors. Numerical ability, the discipline of a student, and interest in learning a few factors relate to learning outcomes. This research aims to know if there is a real and significant of relationship numerical ability, the discipline of a student, and interest of learning with students mathematics learning outcomes in class VII in Muhammadiyah Junior High School 9 Yogyakarta (SMP Muhammadiyah 9 Yogyakarta) regency of even semester in the academic year of 2016/2017. The sample population in SMP Muhammadiyah 9 Yogyakarta in the academic year 2016/2017 consists of 5 classes. A sample class is a class VII A with using random sampling. The technique of the data collection method a questionnaire method and the test method. Data collection instruments using a numerical ability test, questionnaires discipline of student, questionnaires interest of learning, and mathematics achievement test. Test research instruments used validity, different test power, and reliability test. Analysis prerequisite test, including normality test, linearity test, and independent test. Data analysis for hypothesis testing using simple correlation analysis and multiple regression analysis. The results showed a positive and significant relationship between numerical ability, the discipline of a student, and interest in learning of mathematics learning outcomes. The significant level of 5%, Â Â and Â with multiple correlation coefficient of R = 0,866, and multiple regression equation their variables is . Donations are relatively X1=60,958%, X2=38,846%, X3=0,196%, with multiple determination coefficient of 0,750 and the effective contribution X1=45,688%, X2=29,115%, X3=0,147%.